2011
DOI: 10.1007/s12017-011-8159-5
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Brain-Derived Neurotrophic Factor Gene Polymorphisms and Body Weight Change in Schizophrenic Patients Under Long-Term Atypical Antipsychotic Treatment

Abstract: Schizophrenic patients treated with atypical antipsychotics (AAPs) often develop excessive body weight gain, which may lead to further morbidity and poor treatment compliance. This study examined whether genetic variants in the brain-derived neurotrophic factor (BDNF) gene may be associated with body weight change after AAP treatment. The study included 481 schizophrenic patients treated with clozapine (n = 266), olanzapine (n = 79), or risperidone (n = 136) for an average of 49.2 ± 28.2 months. Three common s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…BDNF has also been tested within AIWG with various lines of evidence suggesting involvement of reduced serum levels, and polymorphisms such as rs11030101, rs1519480, and Val66Met in mediating weight gain [445][446][447][448] . In spite of this work, there are no studies, to the author's knowledge, that have tested the epistatic effects between cytokine and BDNF polymorphisms on AIWG.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF has also been tested within AIWG with various lines of evidence suggesting involvement of reduced serum levels, and polymorphisms such as rs11030101, rs1519480, and Val66Met in mediating weight gain [445][446][447][448] . In spite of this work, there are no studies, to the author's knowledge, that have tested the epistatic effects between cytokine and BDNF polymorphisms on AIWG.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, carriers of the rs6265G-rs1519480A haplo type were over-represented among 135 European patients who gained more than 7% weight (p = 0.007) and showed significant AIWG using quantitative analyses (p = 0.015; n = 134) over the course of 6 weeks [76]. In the second study including 481 Taiwanese patients, homozygotes carrying a triallelic haplotype consisting of rs6265G-rs11030101T-rs12291186A gained significantly more weight than patients with one or no copies (p = 0.047) [94]. This study also identified a modest effect of rs11030101 on weight change (p = 0.037), in that TT homozygotes gained more weight (11.3 ± 18.0%) than AT or AA genotypes (4.6 ± 16.3% and 2.9 ± 15.4%, respectively; Supplementary table 1).…”
Section: Bdnfmentioning
confidence: 99%
“…The Val66Met (rs6265) variant is the most extensively studied polymorphism, but has yielded conflicting allelic associations with AIWG [10,93]. Since March 2011, there have been two prospective studies reporting nonsignificant associations [76,94]. However, both groups identified significant haplotype associations of Val66Met with various other markers.…”
Section: Bdnfmentioning
confidence: 99%
“…On the other hand, it might be assumed that some of these clinical consequences, particularly comorbid substance use disorders and physical health impairments, are also the source of allostatic load creating a vicious cycle. may predict weight gain associated with antipsychotic treatment (Lane et al, 2006;Tsai et al, 2011;Zai et al, 2012;Zhang et al, 2007Zhang et al, , 2008. In addition, it has been found that life style modification to reduce body weight increases BDNF level in non-diabetic schizophrenia subjects (Guimaraes et al, 2008;Kuo et al, 2013).…”
Section: Neurotrophinsmentioning
confidence: 99%